A Novel Allele of GmSACPD‐C Associated with High Seed Stearic Acid Concentration in an EMS‐Induced Mutant PE980 in Soybean. Issue 1 (1st January 2018) - Jeong, Jae‐Eun; Kulkarni, Krishnanand P.; Chang, Jeong Ho; Ha, Bo‐Keun; Kang, Sung Taeg; Bilyeu, Kristin; Jo, Hyun; Song, Jong Tae; Lee, Jeong‐Dong
ABSTRACT: Stearic acid is a relatively minor component of soybean [ Glycine max (L.) Merr.] seed oil. Increasing the stearic acid concentration is desired for industrial and food applications, as well as enhanced oxidative stability of the oil. Several ethyl methane sulfonate (EMS)‐induced mutants with elevated seed stearic acid concentration have been reported in soybean. Such mutants were often found to carry alterations in the GmSACPD‐C gene encoding Δ9‐stearoyl‐acyl carrier protein‐desaturase, the enzyme that catalyzes the conversion of stearic acid to oleic acid in the fatty acid biosynthetic pathway. In the present study, we identified a new GmSACPD‐C allele in an EMS‐induced high‐stearic‐acid mutant PE980. The mutant showed a seed stearic acid concentration of ∼160 g kg −1, fourfold that of the wild‐type 'Pungsannamul'. A single base substitution from guanine to adenine at genomic position 703 of first exon of the GmSACPD‐C gene was identified through sequencing, and validated by cosegregation analysis of 167 F2 plants using an allele‐specific SimpleProbe marker. The mutation caused a valine to methionine (+70 position) change in the predicted GmSACPD‐Cprotein sequence. The sequence alignments and three‐dimensional structure modeling of GmSACPD‐C showed that the V70M mutation affects substrate binding and dimerization to reduce enzyme activity. Since the mutant showed significant reductions in seed yield compared with the wild type, marker‐assisted backcrossing may be needed to reduce the yield gap.